Dietary DNA metabarcoding reveals seasonal trophic changes among three syntopic freshwater trout species. (7th December 2020) - Hoenig, Brandon D.; Trevelline, Brian K.; Nuttle, Tim; Porter, Brady A.
Abstract: Providing taxonomically precise dietary characterisations for freshwater fish species is critical for gaining a deeper understanding of the trophic dynamics present in freshwater ecosystems. However, our current understanding of freshwater trophic ecology has relied almost entirely upon direct observation of foraging attempts or morphological identification of partially digested prey. Due to the limitations of morphological dietary characterisations of soft‐bodied arthropod prey, these techniques offer dietary descriptions that can lack satisfactory taxonomic resolution and may bias our interpretations of freshwater food webs. Recent advancements in DNA‐based prey identification have allowed for species‐level prey characterisations for many terrestrial insectivores, although these techniques have seldom been applied to understand the diets of freshwater fish. This study used DNA metabarcoding with high‐throughput, next‐generation sequencing to provide species‐level descriptions of prey composition for three naturally reproducing, syntopic freshwater trout species. Our study supports previous findings that suggested that brook trout ( Salvelinus fontinalis ), brown trout ( Salmo trutta ), and rainbow trout ( Oncorhynchus mykiss ) are generalist predators that display a high degree of seasonal dietary flexibility. Prey composition varied significantly across sampling periods, with detection frequency of terrestrial prey greater in the spring/summer period compared to the autumn period. Pollution‐sensitive aquatic macroinvertebrates were detected frequently across both sampling periods, highlighting the importance of high‐quality streams that support such arthropod prey. DNA metabarcoding also detected a high richness of soft‐bodied, Lepidoptera prey species, a taxonomic group that has been largely underrepresented in previous trout dietary studies that used traditional morphological techniques. This study demonstrates the applicability of dietary DNA metabarcoding for the detection and species‐level identification of arthropods found in freshwater fish lavage samples and highlights the importance of taxonomically precise techniques when attempting to better understand trophic interactions within freshwater communities.